Bodhicitta: an Interpretation - Коробов, Владимир (Acta Orientalia Vilnensia, 2001)
One of the principal objectives of the present work is to draw attention to a very extensive and important for understanding of Buddhist philosophy and practice Mahayana tenn - Bodhicitta. The interaction of its semantic field with the semantic fields of other principal Buddhist concepts (prajñā, śūnyatā) is examined in sufficient detail. The tenn Bodhicitta is discussed in the context of modern conception of intentionality as it is given in phenomenology and contemporary analytic philosophy. Moreover, the author makes an attempt to describe a practical meaning of the tenn Bodhicitta as an agent in the work with different states of mind using topological models.